Cardioprotective effects of compound ALM-802 on subendocardial ischemia models - I. B. Tsorin; V. V. Barchukov; M. B. Vititnova; A. M. Likhosherstov; G. V. Mokrov; S. A. Kryzhanovskii (LLC "Publisher OKI", 2021)
The investigation purpose. N1-(2,3,4-trimethoxybenzyl)-N2-{2-[(2,3,4-trimethoxybenzyl)amino]ethyl}-1,2-ethanediamine (ALM-802 compounds) cardioprotective effect has been studied in rat models of subendocardial ischemia caused by isoproterenol and dobutamine. Material and methods. Acute subendocardial myocardial ischemia in anesthetized rats (urethane 1300 mg/kg, i.p.) was caused by infusion of isoproterenol (20 µg/kg/min i.v.) or dobutamine (80 µg/kg/min i.v.). Results. It was shown that in anesthetized rats, isoproterenol and dobutamine caused almost the same ST-segment depression in the II standard ECG lead. The compound ALM-802 (2 mg/kg i.v.), administered 2 minutes before the infusion start of isoproterenol or dobutamine, equally prevented the occurrence of ischemic changes on the ECG. Conclusion. The non-selective beta-adrenomimetic isoproterenol and the selective β1-adrenomimetic dobutamine cause subendocardial ischemia of the same intensity in anesthetized rats. The compound ALM-802 has a pronounced anti-ischemic effect on both models.